Export Enhancing Effects of Information and Communication Technologies: Evidence from Bangladesh - Islam, Md Shariful; Haque, Md Ziaul; Islam, Syed Nazrul; Alam, Md Mahbubul; Hassan, Abir (Asian Journal of Empirical Research, 2022)
The study examines the impact of information and communications technology (ICT) on bilateral export flows from Bangladesh to its trading partners based on an augmented panel gravity model. It includes 108 importers of Bangladeshi goods. The sample period extends from 2000 to 2018. Primarily, we employ Pooled Ordinary Least Square (POLS) model, and we utilize Poisson Pseudo Maximum Likelihood (PPML) as an alternative estimation technique to check robustness. The findings from the OLS model indicate that ICT has positive and significant effects on Bangladesh’s bilateral export. The results from PPML also support the findings from the OLS model. Therefore, the results come out to be robust. These findings imply that by reducing trade-related costs e. g., shipping costs, market access costs, and communication and information costs, ICT growth in Bangladesh as well as in its trading partner countries enhances trade flows and therefore has a trade-boosting effect.